Optimasi Formula Tahu Lembut Instan dan Rasio Air Rehidrasi dalam Pengembangan Wedang Tahu sebagai Pangan Fungsional - Nurheni Sri Palupi; Nida Raihana Zhafira; Budi Nurtama (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2019)
Soft tofu dessert is a traditional food which is known due to its health benefits. Nowadays, people are not only considering the health benefits of food but also its practicality and shelf life. The development of instant soft tofu dessert is expected for solving the problem. Instant soft tofu dessert is a mix of instant soft tofu and ginger drink. The objective of this study was to obtain the optimum formula and rehydration ratio of instant soft tofu, identify the sensory, chemical, physical characteristics of instant soft tofu dessert, and determine the antioxidant activity of instant soft tofu dessert. Optimization of instant soft tofu’s formula and rehydration process was conducted by using Response Surface Methodology (RSM) with the variables were the concentration of soymilk powder, carrageenan, and volume of water. Responses that was measured were hardness, gummine ss and chewiness. The result of optimal formula and rehydration process consisted of 93.2% soybean powder, 6.8% carrageenan and water volume ratio was 1:8. The hardness of optimal soft tofu was 154.60 gf, gumminess was 28.53 gf, and chewiness was 16.16 gf. Consumption of soft tofu dessert in 38 g serving size generated energy 175.78 kkal, 19.55% AKG of protein, 9.52% AKG of fat, and 5.50% AKG of carbohydrate. The antioxidant activity of instant soft tofu dessert was 16.16 ppm AEAC (ascorbic acid equivalent antioxidant capacity). The result of sensory test of color, flavour, texture, and overall attributes showed that the panelist preference for instant soft tofu dessert is higher than the traditional soft tofu dessert significantly (p<0.05).